Isolated unilateral absence of the right pulmonary artery in two cats visualized by computed tomography angiography. Issue 2 (October 2016) - Jordan, Tyler JM; Scansen, Brian A; Kent, Agnieszka M; Hitchcock, Lora S; Russell, Duncan S
Case series summary: Two cats were evaluated for progressive exercise intolerance, dyspnea and unilateral infiltrate of the left lung. Computed tomography angiography (CTA) revealed absence of the right pulmonary artery in both cats with systemic arterial collateral vessels perfusing the right segmental pulmonary arteries. In one case, the collateral vessels arose from the esophageal artery, while in the other case they derived off the right costocervical trunk. One cat was diagnosed with pulmonary hypertension and was euthanized owing to progressive respiratory distress despite medical management with sildenafil, pimobendan, clopidogrel and furosemide. The other cat, without echocardiographic evidence of pulmonary hypertension, was successfully managed with furosemide and enalapril for more than 4 years. Relevance and novel information: CTA allowed visualization of a rare congenital heart malformation, unilateral absence of the right pulmonary artery, in two cats and accurately characterized the source of collateral blood supply to the affected lung. Severe pulmonary hypertension may be a negative prognostic factor in cats with this condition as medical therapy in the cat without evidence of pulmonary hypertension resolved clinical signs, while the cat with severe pulmonary hypertension died from the disease.